2021
DOI: 10.1177/00368504211059976
|View full text |Cite
|
Sign up to set email alerts
|

MRA improves sensitivity than MRI for the articular-sided partial-thickness rotator cuff tears

Abstract: Background: This study aims to compare the diagnostic accuracy of magnetic resonance imaging (MRI) and MR arthrography (MRA) for the articular-sided partial-thickness rotator cuff tear (PTRCT). Methods: Three electronic databases, PubMed/Medline, Embase and Cochrane Library, were utilized to retrieve articles comparing the diagnostic value of MRA and MRI for detecting articular-sided PTRCTs. The pooled statistical indexes included sensitivity, specificity, positive/negative predictive value, diagnostic odds ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…MRI can more accurately evaluate the size and shape of tendon tears, degree of tendon tear retraction, and tendon and muscle quality ( 45 ). MR arthrography is more sensitive than plain MRI for the diagnosis of articular-sided partial-thickness rotator cuff tears ( Figure 13 ) ( 46 ).…”
Section: Upper Extremitymentioning
confidence: 99%
“…MRI can more accurately evaluate the size and shape of tendon tears, degree of tendon tear retraction, and tendon and muscle quality ( 45 ). MR arthrography is more sensitive than plain MRI for the diagnosis of articular-sided partial-thickness rotator cuff tears ( Figure 13 ) ( 46 ).…”
Section: Upper Extremitymentioning
confidence: 99%
“…While acute trauma can cause rotator cuff tears, the condition often develops progressively over time, primarily due to degenerative changes associated with aging, vascular insufficiency, and intrinsic tendon degeneration. Irrespective of the etiology, accurate and timely diagnosis of rotator cuff tears is of paramount importance in guiding appropriate treatment decisions and optimizing patient outcomes ( 6 , 7 ). The size of rotator cuff tears is a critical factor in determining the appropriate course of clinical management, particularly regarding surgical intervention ( 7 ).…”
Section: Introductionmentioning
confidence: 99%
“…Small tears may often respond well to conservative treatments, such as physical therapy and anti-inflammatory medications, while larger tears often necessitate surgical repair to restore function and alleviate pain. Accurate measurement of tear size is thus essential for determining the most suitable treatment approach ( 6 , 8 , 9 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pain intensity is directly correlated with the presence of kinesiophobia. Recently, multiple studies [ 11 , 12 ] have focused on the shoulder pain caused by partial-thickness rotator cuff tears, and indicated that compared with interstitial and articular-sided partial-thickness RCTs, bursal-sided tears can result in more severe shoulder pain. However, the effect of kinesiophobia on postoperative function was not evaluated.…”
Section: Introductionmentioning
confidence: 99%